Professor Gregory: From Shamans of Jajarkot to Dr. Govinda KC’s Hunger Strike Research - Subedi, Madhusudan (Dhaulagiri Journal of Sociology and Anthropology, 2023)
Loss of a loved one is deeply emotional. This obituary paper is about Professor Gregory G. Maskarinec (May 16, 1951-June 16, 2022), a true friend, an academic intellectual and an honest researcher of medical anthropology. Working with him and sharing ideas with open mind was a great opportunity for me and many scholars in Nepal. Based on collaborative work, interaction and the interview with Professor Gregory, in his remembrance, I have highlighted his academic background and work experiences, friendship and collaborative work, my privilege and opportunities to write about him for his professorship and some of the dreams that could not happen due to his sudden demise. My deepest sympathies are with his family.